How to Organize the Medical Data of Chronically Ill Patients in the Computer - Martín, J. M.; Jabot, F.; Marrel, P. (Methods of Information in Medicine, 1985)
The problems of aiding in the medical decision-making process are very important today, especially through the use of artificial intelligence methods. Before studying these problems, it is necessary to have an excellent availability of relevant medical patient health data as well as medical knowledge.The computer is well adapted for the task of satisfying this essential condition; but in order to accomplish this goal, it is necessary to develop an efficient system of data organization.The current system of sequential organization of medical histories is most likely not the best possible method of data filing. Furthermore, at the present time there are only a small number of relations (in the mathematical sense) between these health data. This situation is not favorable to the development of a relational data base.This article proposes an organization of health data which is relative to the patient. The organization is based on the notion of a medical entity and on the three-dimensionality of health data.
Keywords: Organization of Data; Health Data; Time; Computer